SPIRITUAL AND HISTORICAL SHRINES OF TURGAI REGION - Bekmagambetov, R.; Kozhamberdiev, S. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
In this article, the spiritual and historical shrines of the Turgai region are considered, because in the whole world there is growing interest in sacred places and in general to the cultural landscapes of the native land. It is also worth noting that the study of the region at all times is relevant, as it is aimed at the formation of a system of values, the preservation of its culture, the observance of traditions and the preservation of its own national code.
Keywords: spiritual values; history; national code; historical sites; monuments